1990
DOI: 10.1073/pnas.87.2.777
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of interleukin 3 mRNA expression in mast cells occurs at the posttranscriptional level and is mediated by calcium ions.

Abstract: Interleukin 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(78 citation statements)
references
References 38 publications
(48 reference statements)
4
74
0
Order By: Relevance
“…It has been shown that Fc⑀R-mediated elevation of [Ca 2ϩ ] i is required for cytokine production at transcriptional levels (46,47). An increase in intracellular Ca 2ϩ concentration activates protein phosphatase calcineurin, leading to nuclear translocation of the transcription factor NFAT (48,49).…”
Section: Plc␥2-deficient Mast Cells Have Impaired Degranulation But mentioning
confidence: 99%
“…It has been shown that Fc⑀R-mediated elevation of [Ca 2ϩ ] i is required for cytokine production at transcriptional levels (46,47). An increase in intracellular Ca 2ϩ concentration activates protein phosphatase calcineurin, leading to nuclear translocation of the transcription factor NFAT (48,49).…”
Section: Plc␥2-deficient Mast Cells Have Impaired Degranulation But mentioning
confidence: 99%
“…However, in only a few instances have the AU-rich sequences been shown to function effectively as determinants of decay, and in these cases the features of the AREs that are critical for their function have not been well defined (2,17,22,24,35,37,44,51,54). Because the key features of AREs that contribute to their efficacy as instability determinants are not known, it has been difficult to predict if a particular AU-rich sequence that is present within the 3Ј UTR of an mRNA actually functions as an mRNA-destabilizing sequence.…”
mentioning
confidence: 99%
“…Furthermore, several groups have recently identified a number of mRNA-binding proteins with AU specificity (5-10), two of which have been cloned (11,12). Physiological calcium-dependent interleukin 3 (IL-3) production during IgE-triggered mast cell activation involves mRNA stabilization (13,14), and tumors derived from v-Hras-expressing mast cells were found to have a defect in IL-3 mRNA degradation (15,16). Such IL-3 transcripts could be destabilized by cyclosporin A through a mechanism depending on an intact ARE (16).…”
mentioning
confidence: 99%